In-Trastuzumab Scintigraphy in HER2-Positive Metastatic Breast Cancer Patients Remains Feasible during Trastuzumab Treatment - Sietske B.M. Gaykema; Johan R. de Jong; Patrick J. Perik; Adrienne H. Brouwers; Carolien P. Schröder; Thijs H. Oude Munnink; Alphons H.H. Bongaerts; Elisabeth G.E. de Vries; Marjolijn N. Lub-de Hooge (Molecular Imaging)
Human epidermal growth factor receptor (HER)2 imaging with radiolabeled trastuzumab might support HER2-targeted therapy. It is, however, frequently questioned whether HER2 imaging is also possible during trastuzumab treatment as the receptor might be saturated. We studied the effect of trastuzumab treatment on 111 In-trastuzumab uptake. Patients received trastuzumab weekly and paclitaxel once every 3 weeks. 111 In-trastuzumab was injected on day 1 of cycle 1 and day 15 of cycle 4. Whole-body planar scintigraphy was acquired at different time points postinjection. Tumor uptake and organ distribution between the first and repeated scan series were calculated via residence times. Twenty-five tumor lesions in 12 patients were visualized on both scintigraphy series. Tumor uptake decreased (19.6%; p = .03). The residence times of normal organs remained similar except for the cardiac blood pool (+ 16.3%; p = .014). Trastuzumab treatment decreases tumor 111 In-trastuzumab uptake around 20%. HER2 imaging is feasible during trastuzumab treatment.